KARAKTERISTIK BAHASA KELUARGA MUDA BERDASARKAN PERBEDAAN GENDER DI KECAMATAN TUNJUNGAN KABUPATEN BLORA - Kurnianingsih, Inna Washila (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Language characteristics in young families cannot be separated from social situations and social interactions that exist in society. Apart from that, there are gender of language users who influence the choice of language used. The aim of this study is to analyze the characteristics of the language used in the interaction of young families in Tujungan district, Blora Regency and analyze what factors influenced other than gender differences. The data collection method used is the refer method. The data analysis method used is the extralingual equivalent method. Based on the results of data analysis, the language characteristics of young families in Tunjungan district, Blora Regency can be seen based on the gender differences which can be characterized into male and female speakers. Male language characteristics are based more on masculine traits, which are more aggressive, master of speech, brave, and fierce. The characteristics of female language are less assertive, unclear expression use figurative words more often), and careful in saying something. Factors that influence language choice in young family interactions other than gender differences are ethics / social norms, level of familiarity, speech situation, speech topic, and location of speech.